Relationships among Lifestyle Awareness, Age, and Lifestyle-related Diseases in Healthy Japanese Community Residents - Masayo Nagal (JMIR Publications, 2020)
Purpose: It is widely known that the risk of lifestyle-related diseases can be reduced by reviewing lifestyles, and a variety of efforts for their prevention, such as health education, are being implemented. This study examined community residents' lifestyle awareness, examining their views on their health and lifestyles, age, and lifestyle related diseases. Methods: Study subjects were 180 healthy people (28 men and 152 women) who participated in a health checkup. Participants answered a questionnaire about their awareness of health and lifestyle and their views of disorders. Subsequent measurements of speed of sound (SOS), acceleration plethysmography (APG), and visceral fat area (VFA) were also obtained. Results: The results of the study suggest that age was correlated with some health-related attitudes and behaviors. When health awareness among members of a group is high, it is necessary to provide them with the required information and continuing intervention to motivate them to continue their health improvement. Conclusion: It seems that health awareness influences lifestyle, and its improvement slows the progress of lifestyle related diseases and reduces the effects of aging.